Afghanistan. Antiker Bergbau und Kulturelles Erbe. Die Arbeiten der Jahre 2013 bis 2017 - Boroffka, Nikolaus; Steiniger, Daniel (e-Forschungsberichte des DAI, 2018)
The DFG-Project “RESAF – Ressources and antique mining in Afghanistan”, began in June 2017 as a continuation of the research supported so far by the German Foreign Ministry. The development of the geo information systems (GIS) and the database for archaeometallurgy and mining in Afghanistan are basic aims of the project. Moreover, the documentation and protection of endangered cultural heritage sites and archaeological finds are central topics, as well as capacity building in workshops and trainee programmes for Afghani colleagues held in Germany, are crucial to support sustainable local archaeological work and heritage management in the country.